Eight Surgical Interventions for Lumbar Disc Herniation: A Network Meta-Analysis on Complications - Wei, Fei-Long; Li, Tian; Gao, Quan-You; Yang, Yi; Gao, Hao-Ran; Qian, Ji-Xian; Zhou, Cheng-Pei (Frontiers in Surgery, 2021)
Objective: Therapeutic options for lumbar disc surgery (LDH) have been rapidly evolved worldwide. Conventional pair meta-analysis has shown inconsistent results of safety of different surgical interventions for LDH. A network pooling evaluation of randomized controlled trials (RCT) was conducted to compare eight surgical interventions on complications for patients with LDH. Methods: PubMed, Embase, and the Cochrane Central Register of Controlled Trials (CENTRAL) were searched for RCT from inception to June 2020, with a registration in PROSPERO (CRD42020176821). This study is conducted in accordance with Cochrane guideline. Primary outcomes include intra-operative, post-operative and overall complications, reoperation, operation time, and blood loss. Results: A total of 27 RCT with 2948 participants and eight interventions, including automated percutaneous lumber discectomy (APLD), chemonucleolysis (CN), microdiscectomy (MD), micro-endoscopic discectomy (MED), open discectomy (OD), percutaneous endoscopic lumbar discectomy (PELD), percutaneous laser disc decompression (PLDD), and tubular discectomy (TD) were enrolled. The pooling results suggested that PELD and PLDD are with lower intra-operative and post-operative complication rate, respectively. TD, PELD, PLDD, and MED were the safest procedures for LDH according to complications, reoperation, operation time and blood loss. Conclusion: The results of this study provided evidence that PELD and PLDD were with lower intra-operative and post-operative complication rate, respectively. TD, PELD, PLDD and MED were the safest procedures for LDH according to complications, reoperation, operation time and blood loss.